Toward an Inclusive, Congruent, and Precise Definition of Autoinflammatory Diseases - Wekell, Per; Berg, Stefan; Karlsson, Anna; Fasth, Anders (Frontiers in Immunology, 2017)
Autoinflammatory disease was introduced as a concept in 1999, demarcating an entirely new group of diseases in clinical, immunological and conceptual terms. During recent years the preconditions for the definition of autoinflammatory conditions have changed. This includes the recent discovery of a number of monogenic autoinflammatory conditions with complex phenotypes that combine autoinflammation with defects of the adaptive and/or innate immune system, resulting in the occurrence of infection, autoimmunity and/or uncontrolled hyperinflammation in addition to autoinflammation. Further, there are strong indications that classical IL-1-driven autoinflammatory diseases are associated with activation of adaptive immunity. As suggested by this development, we are of the opinion that an all-encompassing definition of autoinflammatory diseases should regard autoinflammatory conditions and innate dysregulation as inseparable and integral parts of the immune system as a whole. Hence, in this article we try to advance the conceptual understanding of autoinflammatory disease by, proposing a modification of the definition by Daniel Kastner et al, which allows for a congruent and precise description of conditions that expand the immunological spectrum of autoinflammatory disease.